Securing the Innocence: Safeguarding Children from Sexual Violence in School Environment - Pulungan, Nita Nilan Sry Rezki; Tarigan, Vita Cita Emia; Nugraha, Dinda Adistya; Ghuffran, Mohammad (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
This article aims to protect children from sexually violent crimes in schools. Educational institutions should be a place that brings a sense of comfort and safety after the family environment, but in reality, immoral crimes still occur in the school environment. The violation of children's decency is not only a matter of education but also of a country's national laws, that is why Indonesia is a country of law, therefore the protection of law and   preventing sexual violence against children in schools is vital. important in protecting children's rights. The research we conducted was legal research with a qualitative method using descriptive analysis. Collect data from interviews and observations on issues researched in the field. This study concluded that saying things related to sex in the school environment has the effect of making school a dangerous place for students. Provisions regarding criminal acts for perpetrators of disclosing sexual arrangements in existing regulations in Indonesia may be able to minimize cases that occur.